Species specific behaviour and catchability of gadoid fish to floated and bottom set pots. (8th December 2016) - Anders, Neil; Fernö, Anders; Humborstad, Odd-Børre; Løkkeborg, Svein; Utne-Palm, Anne Christine
Abstract : To increase our understanding of the interaction between fish and baited fishing gear we quantitatively described the behaviour of cod ( Gadus morhua), saithe ( Pollachius virens ), and haddock ( Melanogrammus aeglefinus ) to baited pots in a fjord in northern Norway. Detailed video analyses were made to describe species specific responses and examine the effect of lifting the pot off the bottom. The majority of both cod and saithe approached the pots in an upstream direction, and fish approached floated pots higher in the water column than bottom set pots. Cod tended to approach a pot along the seabed and were more likely to encounter the bottom set pot than the floated pot, whereas saithe more often approached in the water column. The capture efficiency was low for all species, but cod were more likely to be caught than saithe and haddock. Cod showed a high encounter rate, low entrance rate and high escape rate. For saithe, a low encounter rate was the chief factor limiting capture efficiency. The observed differences between cod and saithe were explained by species-specific food-search strategies. No difference in entrance rate, escape rate or catch efficiency between the two pot types were found.